AB0525 T-Lymphocyte Subsets and CMV and EBV DNA in Blood of SLE Patients and Kidney Transplant Recipients. (10th June 2014) - Cavagna, L.; Calarota, S.; Caporali, R.; Chiesa, A.; Scorletti, E.; Adzasehoun, K.M.; Locatelli, F.; Montecucco, C.; Baldanti, F.
Abstract : Background: Infections are important cause of morbidity in SLE. Cytomegalovirus (CMV) and Epstein-Barr virus (EBV) can cause serious complications in immunocompromised subjects. The clinical impact of CMV and EBV infections in SLE patients as well as in the disease progression has not been fully investigated Objectives: To analyze immunological (T-lymphocyte subsets) and virological (viral DNA load) parameters in SLE patients and compare with other group of immunocompromised subjects, such as kidney transplant recipients (KTR) Methods: From February 15th to May 31st 2013 blood was collected from 62 patients (57 females; median age 46.5 years, range 21-76) referring to our Lupus Unit and satisfying the 1997 revised ACR classification criteria for SLE. SLE patients were receiving prednisone, hydroxychloroquine, methotrexate, azathioprine, cyclosporine, mycophenolate mofetil or rituximab. Blood was also collected from 67 KTR (29 females, median age 54 years, range 20-74) at 60 days post-transplant. Immunosuppressive therapy consisted of corticosteroids, tacrolimus, everolimus, cyclosporine or mycophenolate mofetil. 38 healthy subjects (23 females, median age 40 years, range 19-67) were analyzed as controls. T-cell subsets were determined by flow-cytometry. CMV and EBV serostatus was determined by commercial IgG ELISA. Quantification of CMV and EBV DNA was determined by real-time PCR Results: 48 (77%) SLE, 61 (91%) KTR and 26 (68%) healthy subjects had serological evidence of remote CMV infection. 16 (97%) SLE, all KTR and 34 (89%) healthy subjects had serological evidence for remote EBV infection. Both SLE patients and KTR had significantly lower median CD4 + (p<0.0001) and CD8 + (p<0.0001) T-cell count than healthy subjects. Median CD4 + T-cell count in SLE patients was 467, 5 (IQR: 279, 8-682, 5) versus 329 (IQR: 204-577) in KTR (p=0.0562), while the median CD8 + T-cell count in SLE patients was significantly higher than that in KTR (300, 5 [IQR: 199, 0-426, 8] versus 223 [IQR: 110-320], respectively, p=0.0037). CMV DNA was not detected in any of the CMV-seropositive healthy subjects, while CMV DNA was detected in 3/48 (6%; median 200, IQR: 100-1000 copies/ml blood) and in 42/61 (69%, median 6400, IQR: 1113-47338 copies/ml blood) CMV-seropositive SLE patients and KTR, respectively (p<0.0001). EBV DNA was detected in 1/34 (100 copies/ml blood) EBV-seropositive healthy subjects, in 26/60 (43%; median 233, IQR: 100-535, 5 copies/ml blood) and in 8/67 (12%; median 325, IQR: 112, 5-1000 copies/ml blood) EBV-seropositive SLE and KTR, respectively (p=0.0001). In SLE, EBV DNA was observed in 9 out of 20 patients with low levels of immunosuppression (hydroxychloroquine and/or prednisone ≤5 mg/day) and in 18 out of 42 patients with higher levels of immunosuppression (all other immunosuppressants and/or prednisone dosages>5 mg/day) (p=1) Conclusions: A high prevalence of EBV DNA in blood has been detected in SLE patients, whereas CMV DNA is prevalent in KTR. In SLE, EBV DNA was frequently observed also in patients with low levels of pharmacological immunosuppression, thus suggesting that in the setting the risk for infections is related also to disease process itself References: Navarra SV, et al. Lupus 2010 Tsai WP, et al. Rheumatol Int 2012 Ramos-Casals M, et al. Medicine 2008 Smedbråten YV, et al. Clin Transplant 2014 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5936